Analysis of the impact of COVID-19 on the dynamic volatility spillover network in the Saudi stock market - Belkhir, Nadia; Abbes, Mouna Boujelbène (International Journal of Asian Social Science, 2024)
This study investigates the risk spillover among the COVID-19-related news Panic Index, the insurance industry, the Tadawul All-Share Index, and sector indices in Saudi stock market. Volatility spillovers serve as an accurate indicator for the transmission of risk across various sectors. Our empirical findings show that, prior to the outbreak of COVID-19, the Tadawul All-Share stock market played a dominant role as a net transmitter of risk for sector indices, including insurance, media, pharma, retail, transport, and utilities. Furthermore, our analysis demonstrates that the COVID-19 Panic Index exerts significant influence on the net pairwise connectedness, particularly impacting the Tadawul All-Share Index, energy, banking, development, materials, real estate, transport, and utilities sectors. Additionally, our results indicate that the insurance sector acts as a net receiver of spillovers from the utilities, media, pharma, and retail sectors throughout the sample period, affirming the heightened impact of the pandemic on these sectors. The pandemic, being a health-related issue, led to a notable surge in the volatility of sectors associated with health, given their pivotal role in effectively addressing the crisis. These insights carry substantial implications for investors, portfolio managers, and policymakers, shedding light on the potential repercussions of the pandemic on the stock market.